Nitrogen-Doped Biochar As Peroxymonosulfate Activator For Acid Orange 7 Removal - Jannah, Zaeni Julia Raudlatul (2021)
The first study shows the oxygen-functionalized biochar that obtained from biowaste through facile method is the promising catalyst as PMS activator and the second study provides insights into Ndoped biochar preparation with favourable intrinsic and extrinsic properties from biowaste for sustainable pollutant removal via PMS activation.